The Forensic Linguist’s Professional Credentials - Butters, Ronald R. (International Journal of Speech, Language and the Law, 2010)
Under current court practice, it is not difficult for anyone with a PhD in English or linguistics to be allowed to testify as a ‘linguistics expert’ in many types of cases. Linguists and professors of English may, however, find themselves in ethically questionable and professionally embarrassing situations if they attempt to assert expertise in subfields at the margins of their linguistic specialization. This paper briefly describes some such situations and suggests ways in which linguists, through such organizations as the International Association of Forensic Linguists (IAFL), the American Association for Applied Linguistics (AAAL), the International Association for Forensic Phonetics and Acoustics (IAFPA), and the Linguistic Society of America (LSA), can improve the qualifications of linguistics legal consultants without getting into the business of actually licensing experts or attempting to maintain registries of approved forensic experts. A Code of Practice could recommend such attributes of the qualified forensic linguist as specialized publication in forensic linguistics, teaching courses in forensic domains, and active membership in specialized forensic linguistic organizations and professional organizations dedicated to subfields that are most relevant to one’s area of forensic testimony (for example, for trademark expertise, organizations devoted to the study of lexicography). The pros and cons of incorporating credentialing criteria into any ‘Guidelines for Consultants’ are also presented.